Blue Print Website Application as a medium for transparency of Islamic Boarding School Activities at Subulul Huda Islamic Boarding School - Hedi Pandowo; Chanif Sari (Politeknik Negeri Madiun, 2022)
At this time information transparency has become a necessity for education providers, both formal and informal. It is important to provide information to related parties, especially activities carried out by education providers so that the information becomes clearer and avoids biased information. Subulul Huda Islamic Boarding School is one of the Islamic boarding schools in Madiun Regency which provides both formal and non-formal education. Transparency is important for the organizers of Islamic boarding schools as a medium to publish all their activities so that the public obtains valid information and gives trust to the community and other related parties. One of the media used to publicize the activities of Islamic boarding schools is a website. Subulul Huda Islamic Boarding School does not yet have a website, so there is no media to publish all of its activities to the wider public. Therefore, it is necessary to conduct training and assistance in implementing website applications to support the benefits for the Subulul Huda Islamic boarding school. The method used in making this website application uses the codeigniter framework, and boostrap version 4.0 with PHP and Mysql languages. The research uses data collection techniques with interview and documentation methods, as well as the design model used in making this application, namely the waterfall and object-oriented approach. The results of this study are in the form of a website application blueprint.